2008
DOI: 10.1002/pon.1432
|View full text |Cite
|
Sign up to set email alerts
|

Burnout in nurses and physicians working at an oncology department

Abstract: Low level of PA was relatively high among Turkish physicians and nurses working in oncology department compared with previous studies. Younger and single physicians had higher burnout levels compared with older and married ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
109
7
12

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(144 citation statements)
references
References 15 publications
16
109
7
12
Order By: Relevance
“…When compared with other studies that were conducted among other groups of nurses [3,17,18,19,20], the EE and DP scores were similar. However, the PA scores were lower compared to other studies [7,21,22,23,24]. This finding could be explained due to different sample size, hospitals, clinics, units differ from to another.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…When compared with other studies that were conducted among other groups of nurses [3,17,18,19,20], the EE and DP scores were similar. However, the PA scores were lower compared to other studies [7,21,22,23,24]. This finding could be explained due to different sample size, hospitals, clinics, units differ from to another.…”
Section: Discussioncontrasting
confidence: 53%
“…That is, the DP and EE scores decreased with increasing ages. Similar to, some studies showed that the burnout level decreased with the increasing duration of professional life [7,21,24,28]. Contrary to, Erickson and Grove (2008) indicated the level of burnout increased according to increased age and years of experience in nurses [40].…”
Section: Discussionmentioning
confidence: 76%
“…These findings were similar to previous studies. 29,30 Our results male physicians are shown higher D and lower EE subscales than their female physicians; however they feel more accomplished than women. This is probably explained by the cultural characteristics of the image of men in Middle East Countries.…”
Section: Discussionmentioning
confidence: 57%
“…In contrast to previous studies, physicians showed higher levels of EE, D, and lower levels of PA compared to the nurses in our study. 29,[31][32][33] Study of the Keeton and colleagues was to explore factors related with physician career satisfaction, work-life balance, and burnout in department of obstetrics and gynecology. 34 They found that burnout is an important predictor of career satisfaction, control over schedule, and work hours.…”
Section: Discussionmentioning
confidence: 99%
“…Míg a kiégés prevalenciáját és szintjét a házastárs és a gyermekek megléte ugyancsak csökkenti, a társ elvesztése -a depresszióval ellentétben -a kiégés szintjére és prevalenciájára nincs hatással [19,20]. Kifejezetten a kiégésre jellemző védőtényező a munkahelyen eltöltött hosszabb idő.…”
unclassified